2022
DOI: 10.1039/d2en00158f
|View full text |Cite
|
Sign up to set email alerts
|

Sulfolipid density dictates the extent of carbon nanodot interaction with chloroplast membranes

Abstract: Mechanisms of nanomaterial delivery to plant chloroplasts have been explored to improve plant stress tolerance, promote photosynthesis, facilitate genetic engineering, and manufacture self-repairing biomaterials, fuels, and biopharmaceuticals. However, the molecular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…This makes sense as the surface charge of LCO and cell membranes are electrostatically incompatible. For example, K. Kim et al (2022) used quartz crystal microbalance with dissipation monitoring to show that negatively charged nanodots do not interact/adhere to negatively charged plant biosurfaces due to electrostatic incompatibilities. But in terms of nutrient depletion, LCO has been reported to adsorb nutrients like phosphate (Laudadio et al, 2019), which could, in theory, partially explain some of the disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…This makes sense as the surface charge of LCO and cell membranes are electrostatically incompatible. For example, K. Kim et al (2022) used quartz crystal microbalance with dissipation monitoring to show that negatively charged nanodots do not interact/adhere to negatively charged plant biosurfaces due to electrostatic incompatibilities. But in terms of nutrient depletion, LCO has been reported to adsorb nutrients like phosphate (Laudadio et al, 2019), which could, in theory, partially explain some of the disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…The acoustic mass density analysis supports the role of electrostatics in determining the interactions between positively charged PEI-CD and negatively charged pectin. We recently reported that CD interactions with lipid membranes from chloroplasts are also dictated by electrostatic interactions . Similar to native and model plant cell walls, QCM-D analysis demonstrated that only the positively charged CD led to detectable attachment to the chloroplast model and native membranes compared to their negative and neutral counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that CD interactions with lipid membranes from chloroplasts are also dictated by electrostatic interactions. 41 Similar to native and model plant cell walls, QCM-D analysis demonstrated that only the positively charged CD led to detectable attachment to the chloroplast model and native membranes compared to their negative and neutral counterparts. Overall, the high adsorption affinity and acoustic mass density on the pectin layer upon exposure to PEI-CD support the idea that electrostatics plays a key role in the interactions between the positively charged nanoparticles and pectin model cell wall surfaces.…”
Section: Real-time Interactions Of Carbon Dots With Pectin Model Surf...mentioning
confidence: 99%
See 2 more Smart Citations